2009
DOI: 10.1039/b910395c
|View full text |Cite
|
Sign up to set email alerts
|

Effect of aryloxo substituents in ethylene polymerisation by tris(pyrazolyl)borate titanium(IV) complexes containing aryloxo ligands of type, TpTiCl2(OAr)

Abstract: Tris(pyrazolyl)borate titanium(IV) complexes containing aryloxo ligand of type, TpTiCl(2)(OAr) [Tp = HB(pyrazolyl)(3); Ar = 2-(i)PrC(6)H(4), C(6)F(5), 2,6-Ph(2)C(6)H(3)], have been prepared, identified, and the structures of TpTiCl(2)(OC(6)F(5)), TpTiCl(2)(O-2,6-Ph(2)C(6)H(3)) have been determined by X-ray crystallography. The 2-(i)PrC(6)H(4) analogue exhibits especially high catalytic activities for ethylene polymerisation in the presence of methylaluminoxane (MAO), and the activity by TpTiCl(2)(OAr) increase… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(3 citation statements)
references
References 36 publications
0
3
0
Order By: Relevance
“…According to literature reports, with MAO as cocatalyst, the addition of a small amount of alkyl aluminium could normally enhance the catalytic activity of the corresponding system. 99,100 Therefore, the same strategy was adopted for ethylene polymerizations catalyzed by 8a-MMAO at 100 and 120 °C, as expected the addition of 100 equiv. of Al i Bu 3 slightly increased the activity from 1920 kg (mol-Ti h) −1 and 2082 kg (mol-Ti h) −1 to 2148 kg (mol-Ti h) −1 and 2202 kg (mol-Ti h) −1 , respectively (entry 15 vs. 35 and 16 vs. 36).…”
Section: Ethylene Polymerizationmentioning
confidence: 99%
“…According to literature reports, with MAO as cocatalyst, the addition of a small amount of alkyl aluminium could normally enhance the catalytic activity of the corresponding system. 99,100 Therefore, the same strategy was adopted for ethylene polymerizations catalyzed by 8a-MMAO at 100 and 120 °C, as expected the addition of 100 equiv. of Al i Bu 3 slightly increased the activity from 1920 kg (mol-Ti h) −1 and 2082 kg (mol-Ti h) −1 to 2148 kg (mol-Ti h) −1 and 2202 kg (mol-Ti h) −1 , respectively (entry 15 vs. 35 and 16 vs. 36).…”
Section: Ethylene Polymerizationmentioning
confidence: 99%
“…] exhibits very high catalytic activity for ethene polymerization, in combination with MAO. 64 Tetrahedral mono(aryloxido) Ti IV complexes [Ti(O(o-R)Ar)X 3 ] (X = O i Pr, ArO = 2-tert-butyl-4-methylphenoxy; R = CMe 3 , CMe 2 Ph and CH 2 NMe 2 ) have been isolated. Attempts to synthesise the corresponding compound with R = CH 2 OMe, resulted in the unsymmetrical dimer [(2-tert-butyl-4-methyl-6-methoxymethylphenoxy)-TiCl(O i Pr)(m 2 -O i Pr) 2 TiCl(O i Pr) 2 ].…”
Section: Alkoxides Amides Etcmentioning
confidence: 99%
“…are promising candidates, especially in terms of syntheses of new polymers by ethylene copolymerizations as demonstrated by using the aryloxo and the ketimide analogues. , Tris(pyrazolyl)borate group 4 metal complexes, Tp′MCl 3 [Tp′ = tris(pyrazolyl)borate; M = Ti, Zr, Hf], are known to exhibit high catalytic activities for ethylene polymerization in the presence of methylalumoxane (MAO), and that the cationic species, generated in situ from Tp*Zr(CH 2 Ph) 3 [Tp* = HB(3,5-Me 2 -pyrazolyl) 3 ] or Tp Ms * Hf(CH 2 Ph) 3 [Tp Ms * = HB(3-mesitylpyrazolyl) 2 (5-mesitylpyrazolyl) − ] and [Ph 3 C][B(C 6 F 5 ) 4 ], polymerize ethylene . We also recently reported that Tp′TiCl 2 (OAr) [Tp = HB(pyrazolyl) 3 ; Ar = Ph, 2- i PrC 6 H 4 , 2,6-Me 2 C 6 H 3 , 2,6- i Pr 2 C 6 H 3 , 2,6-Ph 2 C 6 H 3 , C 6 F 5 ] exhibited moderate to remarkable catalytic activities for ethylene polymerization in the presence of MAO. , Moreover, the cationic complex, [Tp*TiMe(O-2,6-Me 2 C 6 H 3 )] + [MeB(C 6 F 5 ) 3 ] − ·2THF, polymerized ethylene affording polymer with unimodal distributions…”
Section: Introductionmentioning
confidence: 99%